Gaya Kepemimpinan dan Pola Pengambilan Keputusan dalam Perspektif Bawahan di Rumah Sakit - Azra Zahrani; Alifa Firly Apriliana; Aos Kuswandi (CV. ITTC INDONESIA, 2026)
Leadership style and decision-making patterns exercised by supervisors play an important role in shaping subordinates' perceptions and influencing work dynamics within an organization, including in hospital settings. Previous studies on this topic have generally focused on measuring statistical relationships between variables through quantitative approaches. As a result, the subjective meaning that subordinates attach to their supervisor's leadership style and decision-making process remains rarely explored in depth. This study aims to analyze supervisors' leadership style and decision-making patterns from the perspective of subordinates in a hospital setting. The study employs a qualitative approach with a case study design, with data collected through semi-structured interviews and passive participatory observation of an emergency room nurse selected purposively. Data validity was tested using technique triangulation, while data analysis was carried out through the stages of data reduction, data display, and conclusion drawing. The findings show that subordinates perceive their supervisor's leadership style as a combination of a participative approach in normal situations and an instructive approach in urgent situations. The decision-making pattern tends to be consultative, in which subordinates are involved in the discussion stage while the final decision remains with the supervisor. Involvement in the discussion process, although it does not always determine the final outcome of a decision, is shown to contribute to subordinates' sense of being valued and their work motivation. These findings indicate that leadership style and decision-making that are adaptive to situational context play an important role in building a healthy work climate and working relationship in a hospital setting.